Development of Kenaf bast fiber-based insulation paper for power transformer applications - Umair, Muhammad (2022)
Due to the shortage of wood for paper and other applications, non-wood fibers such as Kenaf are utilized for papermaking. Kenaf bast fiber is known as one of the common non-wood fibers used for this purpose. Currently, there are only a few studies that are carried out for Kenaf papers as solid insulation in transformers. Furthermore, the impact of beating and Polyvinyl Alcohol (PVA) on Kenaf paper is quite limited, necessitating further investigation into its feasibility to improve the physio-mechanical and electrical properties. First, the Kenaf bast fibers were collected locally and pulping was carried out using soda pulping methods. The resulting Kenaf pulp was then subjected to various beating revolutions to improve the pulp's strength properties. The beating process was carried out at 3,000, 6,000, 9,000, and 12,000 beating revolutions. PVA was added to the Kenaf pulp after 12,000 beating revolutions. The internal PVA was carried out by adding PVA at weight percentage concentrations of 3%, 6%, 9%, and 12% after the beating stage. The external PVA was obtained by coating the Kenaf paper with 12,000 beating revolutions with PVA at weight percentage concentrations of 2%, 4%, and 6%. Next, the Kenaf papers with different treatments were examined for the physio-mechanical and electrical performances. Apparent density, Tensile Index (TI), Burst Index (BI), and Tear Index (TeI) measurements were carried out to observe the impact of beating and PVA on the physio-mechanical properties of Kenaf paper. Surface resistivity and dielectric constant were measured to determine the dielectric properties of Kenaf paper. An oil-impregnated Kenaf paper was prepared in Mineral Oil (MO) for the measurement of AC breakdown voltage and Partial Discharge (PD) activities. The AC breakdown voltage measurement was carried out based on spherical electrodes with a diameter of 12.5 mm, with both sides facing each other. A Scanning Electron Microscopy (SEM) image was obtained after the AC breakdown voltage to observe the effect of electric discharge on Kenaf bast fibers. The maximum PD amplitude and PD repetition rate were measured based on a needle-plane electrode configuration at a gap distance of 50 mm for an applied voltage of up to 30 kV. The Partial Discharge Inception Voltage (PDIV) was obtained at different voltage levels. It is observed that beating improves the apparent density, TI, and BI of Kenaf paper due to enhancement of fibrillation in Kenaf bast fibers. The beating decreases the average surface resistivity while the average dielectric constant and AC breakdown voltage increase. The PDIV of Kenaf paper decreases as the beating revolutions increase, while the maximum PD amplitude and repetition rate increase. The addition of internal and external PVA further improves the apparent density, TI, and BI of Kenaf paper. The surface resistivity, dielectric constant and AC breakdown voltages, and strength of Kenaf paper are also enhanced with the internal and external PVA. The PDIV of Kenaf paper slightly decreases with the internal and external PVA. The maximum PD amplitude and PD repetition rates of Kenaf paper slightly increase with internal PVA at all applied voltages but decrease with external PVA at voltages of 20 kV, 25 kV, and 30 kV. The TI and BI of the Kenaf paper increased by 197% and 364% with 6% external PVA. Similarly, the highest AC breakdown voltage is observed for the 3 layers of Kenaf paper with 6% external PVA with a value of 36.30 kV. The highest improvement of dielectric constant can be up to 211% for the Kenaf paper with 12% internal PVA. The findings of this study present the minimum thickness, apparent density, and TeI requirements for solid insulation materials in power transformers. However, the TI of Kenaf paper is slightly lower than the required criteria for power transformers, which can be improved with enhancement materials. On the other hand, the AC breakdown strength of Kenaf paper is higher than Kraft paper, while the dielectric constant is comparable. Based on mechanical and electrical properties, Kraft paper has a potential that can be explored further for use in power transformers.